Therapist and client : a relational approach to psychotherapy - Nolan, Patrick, 1951- (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
'Therapist and Client: A Relational Approach to Psychotherapy provides a guide to the fundamental interpersonal elements of the therapeutic relationship that make it the most effective factor in therapy. Presents the fundamental interpersonal elements that make the therapeutic relationship the most effective factor in psychotherapy Explores and integrates a range of approaches from various schools, from psychoanalysis to body-oriented psychotherapy and humanistic psychotherapies Offers clear and practical explanations of the intersubjective aspects of therapy Demonstrates the pivotal need to work in the present moment in order to effect change and tailor therapy to the client Provides detailed case studies and numerous practical applications of infant research and the unified body-mind perspective increasingly revealed by neuroscience'--
'Therapist and Client: A Relational Approach to Psychotherapy provides an invaluable guide to the fundamental interpersonal elements that comprise the most effective factor in therapy-the therapeutic relationship'--
Cover; Praise for Therapist and Client; Title page; Copyright page; Dedication page; Foreword; Preface; Acknowledgements; Introduction; 1 Applying Findings from Infant Research; Introduction; Intersubjectivity; 2 The Interpersonal Relationship; Introduction; The Evolution of a Relational Approach; The Therapist: Self with Other; Reflecting on Self and Other; Repairing the Relationship; 3 Potential Space, Creativity and Play; Introduction; Intersubjectivity -- the Realm of Potential Space; The Therapeutic Space; Creativity and Play; 4 The Intersubjective Experience; Introduction.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Psychotherapist and patient; Psychotherapy; PSYCHOLOGY -- Psychotherapy -- General; Psychotherapist and patient; Psychotherapy; Electronic books